The Impact of Physical Effort on the Gut Microbiota of Long-Distance Fliers - Ferrari, Elís Domingos; Oliveira, Bruno César Miranda; Creasey, Hannah N.; Romualdo da Silva, Débora R. [UNESP]; Nakamura, Alex Akira [UNESP]; Bresciani, Katia D. Saraiva [UNESP]; Widmer, Giovanni (My University, 2023)
Flying pigeons (Columbia livia) are extensively studied for their physical endurance and superior sense of orientation. The extreme physical endurance of which these birds are capable creates a unique opportunity to investigate the possible impact of long-distance flying on the taxonomy and metabolic function of the gut microbiota. This project was enabled by access to two groups of pigeons raised by the same breeder in the same conditions, except that one group was trained in long-distance flying and participated in multiple races covering a total distance of over 2600 km over a 9-week period. In contrast, the second group did not fly. The fecal microbiota was analyzed using 16S amplicon sequencing, and the taxonomy and metabolic function were inferred from this sequence data. Based on phylogenetic distance and metabolic function, flying and non-flying pigeons were found to harbor distinct bacterial microbiota. The microbiota taxonomy varied extensively between the birds, whereas the inferred metabolic potential was relatively stable. Age was not a significant determinant of the fecal microbiota profile. In flying birds, the metabolic pathways annotated with biosynthesis were enriched, representing 60% of the 20 metabolic pathways that were most closely associated with flying.
Keywords: 16S amplicon sequencing; Columbia livia; metabolic pathways; mothur; PICRUSt2; principal coordinate analysis